An investigation on the effect of Russian wheat aphid (Diuraphis noxia Kurdjumov) population growth and feeding damage on selected barley (Hordeum vulgare L.) cultivars under ambient and elevated CO2 - Sacranie, Sattar Farouk (Rhodes University, Faculty of Science, Botany Department, 2016)
The Russian wheat aphid (RWA) (Diuraphis noxia Kurdjumov) is a major pest of cultivated small grains. It is particularly devastating because of is high reproductive rate which results in the growth of large populations which become damaging to its host plants. Development of resistant barley (Hordeum vulgare L.) cultivars is complicated as resistance is polygenic. As a result, the industry remains at risk now that the RWA has spread throughout South Africa. It has, as recently as, 2013, been identified in the SW Cape, which was previously geographically isolated. This is South Africa"Ÿs principle barley growing region. Now a potentially huge problem exists. Therefore, it is imperative that an alternative to pesticide use is found. Testing potential innate resistance in barley cultivars is thus, critical. In this thesis, I present data on four barely cultivars where I have examined their resistance/ lack of resistance to three known RWA biotypes, RWASA1, RWASA2 and RWASA3. The barley varieties used were two economically important South African malt barley cultivars (S5 and SSG 564) along with two potentially RWA resistant Afghan accessions (CIho 4125 and CIho 4159). The RWA biotype population growth rates on each of the plants were determined over a 14 day period. The aim was to establish baseline data of the effects of RWA population growth on the host plants under ambient CO2 (380 "“ 400 ppm) conditions. The extent of RWA feeding damage was investigated at the cell level by examining saliva deposition and cell disruption using Transmission Electron Microscopy; at the tissue/vascular level using fluorescence microscopy, to determine the extent of callose formation; at a whole leaf level by recording percent chlorosis and leaf roll; and finally, at a whole plant level by measuring biomass loss.The experiments were repeated under elevated CO2 (450 ppm) to model any changes in RWA/plant interaction with respect to future climate change. The effects of an elevated CO2 environment and RWA feeding on host plant foliar N and C:N ratio were compared to ambient CO2 conditions, to provide a clearer picture of the potential nutrient drain that a feeding RWA colony exacts on its host. Of the varieties tested, the CIho accessions performed better than the two SA barley cultivars as the CIho accessions appeared to express a mild antibiosis resistance response as RWA populations, particularly those of RWASA1, were smaller than those observed on either S5 or SSG 564. In addition, less damage was evident in the two CIho accessions due to RWA feeding. II RWASA2 was the most virulent of the three RWA biotypes tested, followed by RWASA3 while RWASA1 was the least virulent. Under elevated CO2 conditions, RWA feeding damage was exacerbated but the trend of biotype virulence remained the same. Higher aphid population sizes were recorded under elevated CO2, meant that even the more resistant CIho accessions were overcome by the increased demand made by the larger aphid colonies on the host plants. The % foliar N data showed that under elevated CO2 aphid-free control plants had increased N levels in their leaves. Increased "food" supply (as shown by the increased N levels) therefore allowed significantly larger aphid populations to develop on the plants exposed to elevated CO2, due to improved nutrient status of the phloem sap taken up by RWA. The knock-on effect of a higher aphid population was increased cell disruption as a result of extensive probing, extensive formations of wound callose, with the result that phloem damage impeded nutrient flow through the vascular tissues which contributed to chlorosis and (eventually plant) death. The major conclusion from this study is that even a mild CO2 elevation resulted in an increase aphid population which may pose a severe and very real threat to a barley crop. Therefore, without effort to identify and deploy resistant barley cultivars, it could well be possible that future barley cultivation in South Africa may no longer be viable.
Keywords: Russian wheat aphid -- Research -- South Africa; Barley -- Disease and pest resistance -- South Africa; Callose; Aphids